Tuning the Orchestra: Transcriptional Pathways Controlling Axon Regeneration - Tedeschi, Andrea (Frontiers in Molecular Neuroscience, 2012)
Trauma in the adult mammalian central nervous system leads to irreversible structural and functional impairment due to failed regeneration attempts. In contrast, neurons in the peripheral nervous system exhibit a greater regenerative ability. It has been proposed that an orchestrated sequence of transcriptional events controlling the expression of specific sets of genes may be the underlying basis of an early cell-autonomous regenerative response. Understanding whether transcriptional fine tuning, in parallel with strategies aimed at counteracting extrinsic impediments promotes axon re-growth following central nervous system injuries represents an exciting challenge for future studies. Transcriptional pathways controlling axon regeneration are presented and discussed in this review.